Effects of China’s land-intensive use on carbon emission reduction: A new perspective of industrial structure upgrading - Wu, Haiyang; Qiu, Yige; Yin, Li; Liu, Shanshan; Zhao, Dongxue; Zhang, Mei (Frontiers in Environmental Science, 2022)
The rapid and disorderly expansion of urban construction land has resulted in massive carbon emissions, intensifying the contradiction between land use and low-carbon development. As an essential tool to increase land use efficiency, whether land-intensive use can balance economic and environmental benefits has emerged as a topical issue. This paper investigates the influence of land-intensive use on carbon emissions and its role mechanism under the perspective of industrial structure upgrading by using a two-way fixed-effects model with provincial panel data from 2008 to 2020 in China. The statistical results reveal that land-intensive use not only reduces carbon emissions but also boosts carbon emission efficiency, which achieves carbon emission reduction from both quantity and quality aspects. The carbon emission reduction effect of land-intensive use is mainly manifested in energy, capital, science, and education factors of land-intensive use. The carbon emission reduction benefits obtained through land-intensive use are more noticeable in regions with higher economic development levels. Land-intensive utilization is mainly responsible for carbon emission reduction through promoting industrial structure advanced quality. Our findings suggest that policy makers shall expedite land intensive use development, appropriately synchronize land use levels across regions, and adequately leverage the role mechanisms of advanced industrial structure as a potent measure to promote carbon emission reduction.